Detection and Quantification of Geobacter lovleyi Strain SZ: Implications for Bioremediation at Tetrachloroethene- and Uranium-Impacted Sites - Amos, Benjamin K. (American Society for Microbiology (ASM), 2007)
Geobacter lovleyi strain SZ reduces hexavalent uranium, U(VI), to U(IV) and is the first member of the metal-reducing Geobacter group capable of using tetrachloroethene (PCE) as a growth-supporting electron acceptor. Direct and nested PCR with specific 16S rRNA gene-targeted primer pairs distinguished strain SZ from other known chlorinated ethene-dechlorinating bacteria and closely related Geobacter isolates, including its closest cultured relative, G. thiogenes. Detection limits for direct and nested PCR were approximately 1 × 10(6) and 1 × 10(4) 16S rRNA gene copies per μl of template DNA, respectively. A quantitative real-time PCR (qPCR) approach increased the sensitivity to as few as 30 16S rRNA gene copies per μl of template DNA but was less specific. Melting curve analysis and comparison of the shapes of amplification plots identified false-positive signals and distinguished strain SZ from G. thiogenes when analyzed separately. These indicators were less reliable when target (strain SZ) DNA and nontarget (G. thiogenes) DNA with high sequence similarity were mixed, indicating that the development of qPCR protocols should not only evaluate specificity but also explore the effects of nontarget DNA on the accuracy of quantification. Application of specific tools detected strain SZ-like amplicons in PCE-dechlorinating consortia, including the bioaugmentation consortium KB-1, and two chlorinated ethene-impacted groundwater samples. Strain SZ-like amplicons were also detected in 13 of 22 groundwater samples following biostimulation at the uranium- and chlorinated solvent-contaminated Integrated Field-Scale Subsurface Research Challenge (IFC) site in Oak Ridge, TN. The numbers of strain SZ-like cells increased from below detection to 2.3 × 10(7) ± 0.1 × 10(7) per liter groundwater, suggesting that strain SZ-like organisms contribute to contaminant transformation. The G. lovleyi strain SZ-specific tools will be useful for monitoring bioremediation efforts at uranium- and/or chlorinated solvent-impacted sites such as the Oak Ridge IFC site.